A Contrastive Analysis of Segmental Phonemes in English and Bungku Language - Azhar, Alvian; Lotulung, Donald R. (Universitas Sam Ratulangi, 2026)
This research aims to identify, classify, and describe the forms of phonemes in English and Bungku language using Roach’s (2009) theory and analyze the differences and similarities of phonemes in English and Bungku language by using Fisiak’s (2009) theory. This research used qualitative descriptive method. The English data were collected from Swadesh vocabularies and the data of Bungku language were taken from three native speakers through interview. The results of this research shows that there are 22 consonant forms and 12 vowel forms in English. In Bungku language, there are 17 consonant forms and 5 vowel forms. The differences and similarities found in amounts of phonemes in English and Bungku language. English has 8 consonants /v/, /z/, /θ/, /ð/, /ʃ/, /ʧ/, /w/, /ɹ/ and and 9 vowels; /ɪ/, /ʊ/, /ə/, /ɜ/, /ɔ:/, /æ/, /ʌ/, /ɑ:/, /ɒ/ which are not found Bungku language, while Bungku language have 3 consonant forms /?/, /dʒ/, /r/ and 1 vowel /a/ found only in Bungku language. The similarities of English and Bungku language show 15 consonants; /p/, /b/, /t/, /d/, /k/, /g/, /f/, /s/, /h/, /w/, /n/, /m/, /ŋ/, /j/, /l/ and 3 vowels; /e/, /i/, /u/ are in similar.